Biometric identification of a person using a multi-parameter automated system (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2020)
The article is devoted to the development of a system for biometric identification of a person by face, fingerprints and voice. Two-dimensional and three-dimensional characteristics of a person's face, taking into account area and volume, were used as informative signs of biometric identification of a person by face. For biometric identification of a person by fingerprints, an FPM10A scanner and an Arduino microcontroller were used.Another type of signs is local. They are also called minutiae (features or special points) - unique features inherent only in a specific imprint, determining the points of change in the structure of papillary lines (ending, bifurcation, rupture, etc.), the orientation of the papillary lines and coordinates at these points. Each print can contain up to 70 or more minutes. For biometric identification of a person by voice, the MFCC and PLP algorithms are used for digital processing and analysis of audio recordings. Various algorithms are used for acoustic analysis of speech: hidden Markov models, a model of a mixture of Gaussian distributions. The result of determining the tone of speech and the content of speech for the purposes of identification by voice is obtained.On the Visual FoxPro DBMS, a “Multiparameter automated system for biometric identification of a person” has been developed.